Analisis Pembelajaran Diferensiasi Berbasis P5 pada Mata Pelajaran IPAS Kelas IV Sekolah Dasar - Anis Arhinza; Sukardi Sukardi; Murjainah Murjainah (Journal on Education, 2023)
The problem in this study is the teacher's difficulties in implementing P5 (the Pancasila Student Profile Strengthening Project). This study aims to find out how P5-based differentiation learning works in class IV elementary school science subjects. The method used in this research is descriptive qualitative method. The results of the study show that on the P5 dimension indicator, faith and piety to God Almighty and noble character in class IV are categorized as good. This is evidenced by the results of the percentage of questionnaires filled in by students 100% of students always pray when starting the learning process. Furthermore, the indicator of global diversity, 37% of students always respect friends who do not understand the lesson. Next, the mutual cooperation indicator, 33.3% of students always work together in group work. Furthermore, the independent indicator of 55.5% of students always takes tests independently according to their abilities. Next, the critical reasoning indicator shows that 37% of students are able to answer questions posed by the teacher. As well as the last creative indicator 40.7% of students are able to turn unused used items into used items. Based on the results of the analysis, it can be concluded that P5-based differentiation learning in class IV Science learning at SD Negeri 222 Palembang is categorized as good. By implementing an independent curriculum in science subjects, it can improve academic and student character.